Los depósitos oxfordiano-kimmeridgianos de la Formación Lotena: nuevas perspectivas en la estratigrafía del Jurásico Tardío de la Cuenca Neuquina, Argentina - Olivera, Daniela Elizabeth (2010)
New micropaleontological and stratigraphical data of the Lotena Formation at Barda Norte locality suggest that the Picún Leufú sub-basin was connected to open marine conditions at least until latest Oxfordian- early Kimmeridgian. These data reinforce the hypothesis of a temporary physical disconnection between the Picún Leufú sub-basin and the Neuquén Basin. The transitional characteristics of the palynological assemblages containing taxa recognized in Argentina since the Late Jurassic and the presence of sporomorphs belonging to the Stereisporites pandoi Zone (late Oxfordian) suggest a latest Oxfordian - early Kimmeridgian age for the analyzed deposits. According to the micropaleontological and stratigraphical analysis, the age of the Lotena Formation in the Picún Leufú sub-basin could span from the middle Callovian to the late Oxfordian-early Kimmeridgian. The microfossils (palynomorphs and foraminifers) suggest a moderate energy marginal- marine environment, located close to the terrigenous source area, and in which salinity varied with changes in freshwater influx.